Memorandum on maternal mortality - Labour Party (Great Britain). Advisory Committee on Public Health
1928-07 1928 1920s 10 pages - 4 - Years Birth Rate Death Rate Maternal Mortality per 1,000 Live births Infant Mortality: 1906-10 26.3 14.7 5.00 117 1911-15 23.6 14.3 5.02 110 1916-20 20.1 14.4 5.80 90 1921-25 19.9 12.2 5.04 76 1926 17.8 11.6 5.14 70 The still-birth rate remains throughout this period at over 3 per cent. The reduction in neo-natal deaths has been only from 41 to 32 per 1,000 births during this period. Action taken to prevent maternal mortality might lead to the saving of much infant life under these heads. First confinements involve more risk to the mother, and the fall in the birth rate brings with it a larger proportion of these, and therefore has some effect in maintaining the maternal mortality rate at its present high level. Puerperal sepsis is regarded as the most important single cause of maternal mortality, and in this respect the County Boroughs have a higher record than the Urban or Rural districts. Maternal deaths from other causes are highest in Rural districts. The London rate for puerperal sepsis is second only to the County Boroughs, but in other respects the rate in London is remarkably low. The following table shows maternal death rates per 1,000 live births for 1926, according to nature of district and cause of death:- Sepsis Other causes All causes London 1.61 1.74 3.35 County Boroughs 1.81 2.52 4.33 Other Urban Districts 1.50 2.64 4.14 Rural Districts 1.38 2.76 4.15 All areas. 1.60 2.52 4.12 292/824/1/121